Building Bridges: Public Research Initiatives in Public Education Implementation of Wellbeing Methodology in the Case study of Harmony Index at Bantul Regency, Yogyakarta - Suriadi, Jadi Suriadi (University of Darussalam Gontor Press, 2024)
This paper presents a comprehensive overview of the findings derived from a public research initiative utilizing the Harmony Index (IHaI) methodology in Bantul Regency, Yogyakarta. The study aimed to assess community perceptions and experiences related to harmony and wellbeing, with a focus on public education initiatives. A participation rate of 40.48% among the targeted 10,000 respondents underscores the success of educational outreach efforts in engaging the community and communicating the significance of the research endeavor. The Harmony Index (IM) score of 7.22, along with 30 Perception, Participation, and Acceptability (PPA) points, all 100% under “significant” category. Non-engaged People (NEP) and a reference value of below 10% for non-engaged individuals is allow all (100%). Qualitative figure is highlights the strong community involvement and overall harmony levels exceeding established benchmarks. Furthermore, qualitative data analysis complements quantitative findings, providing valuable insights into nuanced aspects of harmony-related issues within the region. By disseminating these findings through well-organized scripts and short videos, researchers aim to promote public education and facilitate evidence-based decision-making for positive social change.